Carbon fiber micron film guided uniform plating/stripping of metals: A universal approach for highly stable metal batteries. (10th April 2020) - Du, Yuexiu; Liu, Chongwu; Liu, Yunzhao; Han, Qi; Chi, Xiaowei; Liu, Yu
Abstract: Rechargeable metal batteries are desirable for next-generation high specific energy electrochemical energy storage systems. However, low coulombic efficiency and severe dendrite growth during the stripping/plating of metals (e.g. Li, Na, Zn and etc.) considerably hinder their practical applications. To address the above issues, in this work, a facile, versatile, and scalable approach by means of spray depositing carbon fiber micron film (CFMF) onto metals is developed. The porous, uniform, and highly conductive CFMF firmly attached to metal surface with a scaffold structure is found to effectively guide the uniform plating/stripping of both the Zn metal in aqueous electrolytes and the Li metal in organic electrolytes, thus enabling much higher efficiencies of Zn (98.4%) and Li (99.7%) for the 100th cycle on the CFMF-modified current collectors than those of bare current collectors. And the so far record high cycling stability for the symmetric cells using CFMF/Zn (2500 h) and CFMF/Li (1000 h) electrodes is achieved at 1 mA cm −2 and 4 mA cm −2, respectively. Benefiting from the delicately designed CFMF-modified Zn or Li metal anodes, the full cells of Zn–MnO2 and Li–LiMn2 O4 are rendered excellent rate capability and significantly extended cycle life. Highlights: A versatile and scalable approach was developed to stabilize both Zn and Li. Carbon fiber micron film guided highly reversible plating/stripping of Zn and Li. The modified Zn and Li exhibited record long cycling life in the symmetric cells. The full cells were also render excellent rate capability and cyclability.